PEMBUATAN MEDIA PEMBELAJARAN FISIKA MATERI PEMANASAN GLOBAL BERBASIS PENDIDIKAN KARAKTER - Manda, Fransiska; Saehana, Sahrul (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This research was conducted to produce a video based on character education in physics learning on the topic of global warming. The purpose of this research was to produce a valid and effective character education-based physics learning video media. This research was a development research that refered to the Development and Research Development (DRD) model which includes the preliminary stage, design stage, and effectiveness test stage. The video developed presented contextual examples that were adapted to the student environment at SMP Negeri 21 Palu. It intended to help students to understand physics concepts. Also, it can be used as a reference for teachers to improve the quality of physics learning in developing teaching materials, and is expected to be an additional reference for further research on making character education-based physics learning videos. Based on the results of the analysis of the media expert's assessment, an average score of 3.1 was obtained and was categorized as "Good", the analysis of the material expert's assessment obtained an average score of 3.0 and was categorized as "Good". The results of the study indicate that the developed learning video can be used as one of the learning media for students.